The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1103/physrevc.28.345
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing Fermi—Gamow-Teller mixing in the positron decay ofCo58

Abstract: The asymmetry parameter, 2 p, in the positron decay of polarized "Co has been measured to be +0.341+0.013. Assuming the standard T-invariant V -A weak interaction theory, the Fermi to Gamow-Teller mixing ratio, y =Cl MF/CzMzT, was determined to be -0.005+0.008. The vanishing value of y is consistent with the isospin selection rule for the Fermi matrix element. RADIOACTIVITY "Co; measured P(9), y(()); deduced source P, P asymmetry coefficient, Fermi to Gamow-Teller mixing ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…However, it is unclear whether the quoted error bar is purely statistical or whether systematic errors, such as the remaining scattering of the β particles were also included. Indeed no detailed list of systematic errors was given, while in later works on 56 Co and 58 Co using the same setup systematic errors were addressed in detail and were of the order of a few percent [40,41]. The effect of scattering was clearly demonstrated by these authors by presenting results for a thin and a thick source, which yielded values for the asymmetry parameter that differed by as much as 30 %.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether the quoted error bar is purely statistical or whether systematic errors, such as the remaining scattering of the β particles were also included. Indeed no detailed list of systematic errors was given, while in later works on 56 Co and 58 Co using the same setup systematic errors were addressed in detail and were of the order of a few percent [40,41]. The effect of scattering was clearly demonstrated by these authors by presenting results for a thin and a thick source, which yielded values for the asymmetry parameter that differed by as much as 30 %.…”
Section: Discussionmentioning
confidence: 99%
“…NO measurements of the F-GT mixing ratio for the isospin-forbidden allowed I t = Ij decays of 56 Co and 58 Co were also carried out at Columbia University [11][12]. These ß-decay data yield small Fermi admixtures, as expected.…”
Section: Beta-asymmetry Measurements With Nuclear Orientationmentioning
confidence: 86%
“…A second advantage of the low temperature nuclear orientation technique is that it allows precise and accurate anisotropy information to be deduced by using appropriate source preparation and detection techniques. As an illustration, it has been shown that for ß-asymmetries in most cases a higher signal to background ratio is obtained than with β-γ circular polarization correlation experiments [10][11], This has been indicated by the NO results of the Fermi to Gamow-Teller ratios in ß-decay [11][12].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Since 1956, fourteen measurements [4][5][6][7][8][9][10][11][12][13][14][15][16][17] have been made on the asymmetry coefficient A for 0 + of the 58 Co 58 Fe decay with a view to obtaining y. However, such measurements by either polarized nuclei or jS-y circular polarization correlations in unpolarized nuclei are difficult, and different workers tend to obtain rather different values.…”
Section: Introductionmentioning
confidence: 99%